2017
DOI: 10.1111/aogs.13205
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable mini‐sling compared with conventional mid‐urethral slings in women with urinary incontinence. A randomized controlled trial

Abstract: Introduction. The primary aim of this study was to compare the objective and subjective outcomes and short-term complication rates of an adjustable singleincision mini-sling (SIMS) vs. standard mid-urethral slings (SMUS). The secondary aim was to report pain perception and complications at the oneyear follow up. Material and methods. The study was designed as a multicenter prospective randomized trial where women were included from eight centers in Denmark, Norway and Sweden. The trial was registered at Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Data were recorded following inclusion. The follow-up conducted from inclusion up to 1 year is described in the study by Rudnicki et al [21].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were recorded following inclusion. The follow-up conducted from inclusion up to 1 year is described in the study by Rudnicki et al [21].…”
Section: Methodsmentioning
confidence: 99%
“…The study was designed as a randomized trial and one-sided power analysis that was conducted before randomization showed that the inclusion of 131 women was required in each arm anticipating a cure rate of not less than 9% for Ajust® compared with SMUS (α = 0.05, β = 0.2) [21]. Data were analyzed using descriptive and analytical statistics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] Nevertheless, this procedure was is associated with more complications, prolonged hospital stay and a high rate of anterior vaginal wall prolapse. [ 5 ] Nowadays, Burch colposuspension is replaced by minimally invasive procedures using mesh sling, a new surgical technique with minimal surgical trauma access, performed under local anesthesia, that has been found to significantly improve the quality of life,[ 6 ] similarly to what has been found for native tissue repair[ 7 ] an and other techniques. [ 8 ] Several studies have shown that the transobturator procedure is associated with postoperative pain in the inner thigh, but it shows high percentage of cure rates (up to 90%), shorter operation time, less blood loss as compared to retropubic route.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Several studies have shown that the transobturator procedure is associated with postoperative pain in the inner thigh, but it shows high percentage of cure rates (up to 90%), shorter operation time, less blood loss as compared to retropubic route. [ 5 ] The single-incision mini-sling (SIMS) was introduced in 2008 with the aim to further decrease potential complications from retropubic and transobturator approaches (such as bladder or bowel perforation and vessel injury). [ 9 ] There is no blind passage of the needle introducer through the retropubic space when inserting the tension-free vaginal tape (TVT) nor the passage of trocars through the obturator or adductor muscles when inserting the transobturator tape (TOT).…”
Section: Introductionmentioning
confidence: 99%